Rancang Bangun Sistem Informasi Posyandu untuk Mendukung Pelaporan Online Berbasis Web - Asri Mulyani; Fitri Nuraeni; Astri Yuliastri (Jurnal Algoritma, 2022)
Posyandu activities aim to obtain information about the health developments of posyandu targets including: toddlers, pregnant women and the elderly. During the Covid 19 period, all service activities including Posyandu were limited because significant crowds were not allowed. This affects the current posyandu activities where there are no facilities to facilitate data management, reporting, and delivery of information on posyandu targets in several existing posyandu. This causes data storage to be stored by officers and submission of reports to the puskesmas only via short message media or SMS. Therefore, it is necessary to develop a system to support the posyandu reporting process to the puskesmas. The purpose of this research is to create a posyandu information system that can manage data and report to the puskesmas online. The research method used is the Rational Unified Process (RUP) with the stages of inception, elaboration, construction and transition. This research produces a posyandu information system that can provide information to the public on the target category of posyandu in particular, as well as an information system that can carry out online reporting from the posyandu to related parties such as villages or puskesmas.